Expected Survival Using Models of Life Table Compared with Survival of Gastrointestinal Tract Cancer Patients in North of Iran - H Zeraati; K Mohammad; M Mahmoodi; M Sheikh Fathollahi (Tehran University of Medical Sciences, 2011)
Background: Northern regions of Iran have been encountered to dominate malignancies of gastrointestinal (GI) tract. We came to examine the total excess mortality due to the GI cancer in Mazandaran province.Methods: Socio-demographic and clinical data of 484 patients with GI cancer collected during the years 1990-1991were available from Babol Cancer Registry. Patients were followed up for 15 years by the year 2006. Using the West Coale-Demeny life table model, a number of five life tables for men and four for women, corresponding to each birth cohort, were constructed. Observed survival was obtained using the Kaplan-Meier method and compared with the Expected survival calculated using the direct adjusted method represented by STEIN et al.Results: The sample of subjects encompassed 66.3% men and 33.7% women with mean age 58.26 ± 10.90, and endoscopy was the general method for cancer detection. Esophagus accounted for 74.2%, and stomach and colorectal accounted for 22.7% and 3.1% of GI cancers, respectively. Survival rate in 15 years following diagnosis was nearly 6%. Comparing patient and expected survival curves showed a significantly reduced survival for patients of each GI cancer over the whole period and especially during the first two years after diagnosis.Conclusion: Patients experienced reduced survival associated with the development of GI cancers. Considering individuals in a population come from different cohorts, adjustment by constructing distinct life tables for different birth cohorts is recommended. The West model is recommended as a first choice to represent mortality in countries whose registration systems are exposed to various errors.